CONODONTS FROM THE DUMUGOL FORMATION LOWER ORDOVICIAN, TANYANG AREA, KOREA - Kwang-Soo Seo; Dong-Woo Lee; In-Chang Lyu; Byung-Su Lee (My University, 2002)
This study is to clarify the geologic time of the Dumugol Formation in the Tanyang area on the basis of conodonts. A total of 245 identifiable conodonts were recovered from 56 samples. They are classified into 7 multielement species referable to 10 genera, and 9 form species belonging to 13 genera. In terms of biostratigraphic biozones, the Dumugol Formation is divided into four conodont zones, viz, Chosonodina herfurthi – Rossodus manitouensis, Glyptoconus quadraplicatus, Paracordylodus gracilis, and Triangulodus dumugolensis zones in ascending order. Conodont fauna of the Dumugol Formation is correlated with the Chosonodina herfurthi – Rossodus manitouensis zone to the Triangulodus dumugolensis zone of the Dumugol Formation in the Baegunsan Syncline region, the Cordylodus rotundatus – Acodus oneotensis zone to the Scalpellodus tersus zone of North China, Fauna C to Fauna E of North America, the Cordylodus rotundatus zone to the Oepikodus evae zone of the Baltic region, the Chosonodina herfurthi – Acodus zone to the Drepanodus gracilis – Scolopodus sexplicatus zone in Australia. The Dumugol Formation is Late Tremadocian through Early Arenigian of Europe, Late Ibexian through Early Canadian of North America in age. Most of the recovered conodonts are well preserved and are brownish black (5YR 2.5/1 to 2.5 YR 2.5/1 by Munsell Soil Color), displaying a color alteration index of 4–5 and indicating that these rocks have been heated to 300–400 degrees Celsius.
Keywords: Tanyang; Dumugol Formation; conodont fauna; biostratigraphy; Late Tremadocian; Early Arenigian; Korea; Paleozoic::Ordovician::Lower::Tremadocian; Палеозой::Ордовикская::Нижний::Тремадокский